Analysis of Corruption Enforcement Law on PT Timah Corruption Case as a Form of Corporate Crime - Zabidin; Pratiwi Ayu Sri D; Sri Setiawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Corruption within the corporate sector, particularly in state-owned enterprises, has emerged as a significant concern in the Indonesian legal system. A notable example of this is the corruption scandal at PT. Timah, a state-owned entity in the tin mining industry. This case uncovered instances of authority misuse and budget manipulation by individuals within the company, resulting in harm to both the state and the public. The Law on Corruption Crimes serves as the primary legal framework to address such criminal activities. This article seeks to explore the implementation of this law in the case of PT. Timah and provide insights into the challenges that law enforcement may face in tackling similar cases in the future.